Supernumerary occlusal cusps on permanent human teeth - Kocsis S., Gábor (Acta Biologica Szegediensis, 2002)
Supernumerary (central) cusps that appear on the occlusal surface of the teeth have already been grouped by many authors. The most comprehensive grouping of central cusps on the premolars is that by Schulze (1987). However, different central cusp forms may occur on the molar teeth, and cusp-like protrusions may also develop on the incisors and the canines. In the present work, plaster casts of the teeth of 500 orthodontic patients (250 males and 250 females) were examined for central cusps at the above departments. The central cusps appeared on the dentition of 47.6% of the investigated Hungarian population . From a total of 13,79 3 teeth examined , 501 (3.69% ) were observed to display a central cusp. The teeth most often affected were the mandibular first premolars (11.6%). A new central cusp form , the "margoid central cusp formation," was noted.